Assessment of force decay in orthodontic elastomeric chains: An in vitro study - Kochenborger, Claudia; Lopes da Silva, Dayanne; Marchioro, Ernani Menezes [UNESP]; Vargas, Diogo Antunes; Hahn, Luciane [UNESP] (FapUNIFESP (SciELO), 2012)
Introduction: Elastomeric materials are considered important sources of orthodontic forces. Objective: To assess force degradation over time of four commercially available orthodontic elastomeric chains (Morelli, Ormco, TP and Unitek). Methods: The synthetic elastics were submerged in 37 oC synthetic saliva and stretched by a force of 150 g (15 mm - Morelli and TP; 16mm - Unitek and Ormco). With a dynamometer, the delivered force was evaluated at different intervals: 30 minutes, 7 days, 14 days and 21 days. The results were subjected to ANOVA and Tukey's test. Results: There was a force decay between 19% to 26.67% after 30 minutes, and 36.67% to 57% after 21 days of activation. Conclusions: TP elastomeric chains exhibited the smallest percentage of force decay, with greater stability at all time intervals tested. Meanwhile, the Unitek chains displayed the highest percentage of force degradation, and no statically significant difference was found in force decay between Ormco and Morelli elastomeric chains during the study period.
Keywords: Elastics; Elastomeric chain; Synthetic elastics